Respostas
respondido por:
0
Resposta:
Explicação passo-a-passo:
(x+4)² + 3x = x+26
(x - 1).(x - 1) + 3x = x + 26
x² - x - x + 1 + 3x - x - 26 = 0
x² - x - x - x + 3x + 1 - 26 = 0
x² - 3x + 3x - 25 = 0 cancela - 3x + 3x
x² - 25 = 0
x ² = 25
x = ± √25
x = ± 5
S[- 5 ; + 5]
respondido por:
0
Explicação passo-a-passo:
(x+4)² + 3x = x + 26
x . x = x² 4 . 4 = 16
x² + 16 + 3x = x + 26
x² + 3x - x = 26 - 16
4x² - x = 10
3x² = 10
x² = 10/3
Anexos:
Perguntas similares
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás